THE EFFECT OF EFFLUERAGE STIMULUS ON PAIN IN NORMAL LABOR IN PRAMBONTERGAYANG HEALTH CENTER IN TUBAN REGENCY - Patonah, Siti; Muslima, Evita; Nisa, Siti Khoirun (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2020)
ABSTRACTOne of the things that accompany labor, which is most felt unpleasant and even frightening for mothers is labor pain. There are several nonpharmacological methods that can be applied in reducing labor pain, one of which is a touch of massage. The purpose of this study was to determine the effect of stimulus effleurage on pain during normal delivery at the Prambontergayang Public Health Center in Tuban Regency. Pre-experimental research design with a pretest-posttest design approach. Total population of 15 maternity mothers and a sample of 15 respondents. The sample selection uses nonprobability sampling with accidental sampling technique. Data collection of pain level variables during labor by observation, data processing is done through editing, coding, scoring and tabulating as well as data analysis with cross tables.The results of the study of pregnant women more than half of the mothers before giving an effleurage stimulus had a severe pain level of 10 people (66.67%), after being given an effleurage stimulus less than some had a severe pain level of 2 people (13.33%). The conclusion from the study found that pregnant women are expected to be more active in getting information by visiting health care facilities every month and from seeking information about techniques to reduce pain during labor, especially about stimulus effleurage. Keywords: Effleurage stimulus, pain, maternity